REGULATION OF ECONOMIC ACTIVITY IN THE REGIONS AS A TOOL FOR INCREASING REGIONAL COMPETITIVENESS AND INVESTMENT ATTRACTIVENESS OF MUNICIPALITIES - TSONKOV, Nikolay (Journal of European Economy, 2020)
Author analyzes scientific experience and literature in the field of assessing regional economy and regional development. In this research, the author tries to explore relation between state intervention and investment attractiveness of regions. The author proposes a new Regional Investment Index, which is an instrument for measuring business environment improvement and increase in investment attractiveness. This new Regional Investment Index is an instrument that can be used not only for analysis of economic indicators, but also for improvement of state policy at the regional level. The author develops Regional investment index in order to manage regional development and direction of investment processes. Regional investment index allows for a potential comparison of municipalities by combining different approaches and dimensions and thus becoming unique. The Russian index differs of the Regional investment index because the group of determinants is structured into two indexes. On the other hand, the Asian indexes are ones which are combined and refined in Regional investment index. The new Regional investment index is sophisticated, more flexible, comprehensive and gives more opportunities for comparison at the level of local authorities and territories. JEL: H83, R13, R58.